2012
DOI: 10.1117/12.907887
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity enhancement of in-line chemical sensing device with C-type fiber and photonic crystal fiber

Abstract: The in-line chemical sensing device with novel C-type fiber and photonic crystal fiber was successfully fabricated. We further improved the sensitivity or light coupling efficiency of our in-line chemical sensing device with optimized the Ctype fiber length. The results show that sensitivity and response time of device are significantly enhanced with optimization of cleaving and splicing process. The gas sensing experiments with the optimized conditions are demonstrated for detecting partial pressure of acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…In our previous study [14]- [16], we demonstrated an in-line gas sensor unit by proposing a novel 'C-type' fiber as a fiberized inlet/outlet and a PCF with Ge-doped ring defect as a sensing medium. This configuration could overcome prior limitations in PCF-based optical sensors such as broken symmetry in the periodic structure of the PCF, alignment and coupling difficulties and holes that are too small for efficient fluid entry [17]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [14]- [16], we demonstrated an in-line gas sensor unit by proposing a novel 'C-type' fiber as a fiberized inlet/outlet and a PCF with Ge-doped ring defect as a sensing medium. This configuration could overcome prior limitations in PCF-based optical sensors such as broken symmetry in the periodic structure of the PCF, alignment and coupling difficulties and holes that are too small for efficient fluid entry [17]- [19].…”
Section: Introductionmentioning
confidence: 99%